On Love, the Palestinian Way: Kinship, Care and Abolition in Palestinian Feminist Praxis - Sarah Ihmoud (State Crime, 2024)
This article centres the forms of kinship and care work that Palestinian women perform within and beyond the institution of the colonial prison in occupied territory through an analysis of letters expressing grief, care and radical hope as material expressions of an abolitionist feminist praxis of decolonial love. Women’s letter-writing practices offer a material expression of the sentient life forms that suture the social fabric of the Palestinian collective, regenerating our connections to each other and to our homeland. This analysis invites consideration of decolonial love as a liberatory method through which Palestinians call each other into intimate relation. It argues that attending to this underexplored feminist praxis enacted from within the space of genocidal duress holds the capacity to amplify a Palestinian sensorium that sharpens our capacity to enact revolutionary struggle against Israeli state violence and settler colonial criminality.